Russian Migration and Psychological Aspect - Petruk, Galina V. (2020)
The problem of regional migration is treated in the article. The development of the Far Eastern territories is a priority now. The government has developed many large-scale projects aimed at supporting the remote region, but the problem of emigration of the economically active population has not settled since 1991. The problem of the outflow of promising young personnel from its territory is particularly acute. The purpose of this research is to study the reasons for the migration of young people from the Primorsky Region - one of the regions of the Far East. The main tasks were to obtain visions of migration moods and motivation of migration behavior of students. The study used a psychological verbal-communicative method - a survey in which a specially designed list of questions was used as a means to collect information from the respondent. The survey covered about 1,000 respondents between the ages of 15 and 30.  The research has shown that the main reason for emigration of school graduates is the opportunity to progress, studying in prestigious domestic and foreign universities, working in the largest Russian and foreign companies, that not enough represented here. Excellent and good rated school graduates prefer to enter Moscow and St. Petersburg universities. This means that most prospective workers in the future want to leave the territory of the region. Analysis of the responses of the university graduates revealed the prevalence of negative expectations about their future and the future of the territories. The data indicated that the main reasons to leave the country and the Primorsky Region are low job prospects for university graduates, lack of self-realization possibilities, low wages and the instability of the region’s political and socio-economic situation. In addition, the situation is exacerbated by the fact that respondents, for the most part, do not know about the projects that are being implemented in the region and do not see career prospects, which confirms the implementation of many strategic projects of the region only on paper. The lack of measures to prevent the emigration of young people will have a number of negative economic and social consequences, one of which is the reduction of competitevness of the territory. Creating favorable conditions for young people in the region, active public policy to attract young skilled professionals in Primorye is a prerequisite for the development of the region's intellectual capital and a guarantee of its dynamic socio-economic development.